Maternal sensitivity and its relation to personality traits - Šarkinaitė, Laura; Čekuolienė, Danguolė; Kalinauskienė, Lina (Psichologija, 2007)
This study explored relations between maternal sensitivity and personality traits. Maternal sensitivity refers to a mother’s ability to perceive and to interpret accurately the signals and communications implicit in her infant’s behavior, and given this understanding, to respond to them appropriately and promptly. Maternal sensitivity is of fundamental importance to the development of a secure attachment and also to the further life of the child. Though attachment theory states that a mother’s attachment representations are the principal determinant of maternal sensitivity, the ecological perspective proposes that contextual variables also can affect maternal sensitivity and the relationship between the mother and her child. One of the explored contextual variables in this perspective is mothers’ psychological characteristics, but data in this realm are inconsistent. Inasmuch as psychological traits influence interactions with others, they also may play a role in the early mother–infant interaction and may influence some aspects of maternal sensitivity. The purpose of this study was to determine how maternal sensitivity is related to her personality traits (i.e. introversion / extraversion, adjustment to reality, accuracy of perception, interest in people, and emotionality). Thirty-two mother-infant dyads participated in the study; all infants were firstborns. Maternal sensitivity was assessed using the observation technique (Ainsworth’s Maternal Sensitivity Scale). The Rorschach inkblot test was used for evaluation of mothers’ personality traits. The type of experience (i.e. introversion/extraversion), adjustment to reality, the accuracy of perception, emotionality and interest in people were evaluated. The results suggest that maternal sensitivity is related to her type of experience: mothers that are introverted, are more sensitive to their infant’s signals. Our data also suggest that sensitive mothers tend to appreciate more social standards, they could be better socially adjusted and have more adequate contact with reality than insensitive mothers. Also, sensitive mothers’ evaluations of creativity, the accuracy of perception and concentration of attention tend to be higher than those of insensitive mothers. Data of our study did not confirm any relationship between maternal sensitivity and her emotionality evaluation.
Keywords: attachment; maternal sensitivity; personality traits